Dada as funções com as leis de formação f(x) = 4x – 7 e g(x) = 2x² - 5x + 1, podemos afirmar que f(1) + g(2) é:
a) 4
b) 2
c) 0
d) – 2
e) – 4
Soluções para a tarefa
Respondido por
1
Resposta:
item e) -4
Explicação passo-a-passo:
f(x)= 4x - 7
f(1)= 4.1 - 7
f(1)= 4 - 7
f(1)= - 3
g(x)= 2x² - 5x +1
g(2)= 2.2² - 5.2 +1
g(2)= 2.4 - 10 +1
g(2)= 8 - 10 +1
g(2)= - 2 +1
g(2)= - 1
f(1) + g(2)=
- 3 + (-1)=
- 3 - 1=
- 4
Perguntas interessantes
Matemática,
7 meses atrás
Português,
7 meses atrás
Biologia,
7 meses atrás
ENEM,
8 meses atrás
ENEM,
8 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás